2006
DOI: 10.1016/j.contraception.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Does insertion and use of an intrauterine device increase the risk of pelvic inflammatory disease among women with sexually transmitted infection? A systematic review

Abstract: Concerns exist as to whether the insertion of copper and levonorgestrel-releasing intrauterine devices (IUDs) increases the risk of pelvic inflammatory disease (PID) among women with sexually transmitted infection (STI). We searched the MEDLINE database for all articles published between January 1966 and March 2005 that included evidence relevant to IUDs and STIs and PID. None of the studies that examined women with STIs compared the risk of PID between those with insertion or use of an IUD and those who had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 19 publications
0
84
0
5
Order By: Relevance
“…However, beyond the first 20 days after insertion, IUDs do not increase rates of pelvic inflammatory disease (PID) above baseline. 68,69 Screening for gonorrhea and Chlamydia can be performed at the same time as insertion. 59 Any necessary treatment can be subsequently provided without IUD removal, as international studies have demonstrated that STIs and PID can be treated with the IUD in place, 70 as long as the patient improves with treatment.…”
Section: Intrauterine Contraceptionmentioning
confidence: 99%
“…However, beyond the first 20 days after insertion, IUDs do not increase rates of pelvic inflammatory disease (PID) above baseline. 68,69 Screening for gonorrhea and Chlamydia can be performed at the same time as insertion. 59 Any necessary treatment can be subsequently provided without IUD removal, as international studies have demonstrated that STIs and PID can be treated with the IUD in place, 70 as long as the patient improves with treatment.…”
Section: Intrauterine Contraceptionmentioning
confidence: 99%
“…Decrease in sexual frequency during pregnancy and puerperium might also be a contributing factor for the same. Mohllajee AP et al 12 had found that PID occurs either due to infection introduced during insertion procedure or due to ascent of pre-existing cervical infection. In women who had negative cervical cultures, the risk of pelvic inflammatory disease with IUD placement was 0%-2%, whereas in the presence of infection, it was 0%-5%.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported the risks of PID with insertion of an IUD in the presence of existing infection. With IUD insertion in the presence of Chlamydia infection or gonorrhoea, subsequent PID rates were 0-5%, compared to insertion in the absence of infection (0-2%) 140 . Although trial results do not indicate the need to screen for and treat sexually transmitted diseases before inserting and IUD 141 , it is rationale to suggest that the insertion of an IUD is indicated only in women with negative vaginal cultures ( In cases of vaginal infection, it is possible that the insertion of an IUD carries bacteria into the uterus and traumatizing the endometrium causes several infections.…”
Section: Intrauterine Devices (Iud)mentioning
confidence: 98%